RADIO VARIABILITY OF THE QUASAR 3C 273 ON THE CENTIMETRIC WAVES -WAVELET-ANALYSIS - Ryabov, M. I.; Sukharev, A. L.; Sych, R. A.; Aller, M. F. (Одеські астрономічні публікації, 2012)
3C 273- has been intensively investigated for many years, since opening of quasars in 1963. Since 1965 on radio telescope RT-26 of Michigan University on frequencies 14.5, 8 and 4.8 GHz long monitoring of this radio source have been carried out. Flux variability of a radio emission on studied frequencies consists a trend on which fast flux changes with characteristic time from 1 to 5 years are imposed. Fourier’s methods and the wavelet-analysis that allowed investigating in details changes harmonious component of signals over time are applied. On a trend component the main period makes 8 years. With Fourier filtration have been received <O - C> data, for allocation high-frequency component in studied signals. By the results of calculations of wavelet-spectrums the periods of 3.5 and 2.3 years are revealed. On the basis of calculation of integrated wavelet-spectrums in a frequency range on <O - C> this <spectrum of the periods> characterizing main phases of activity of a source are defined. On the basis of the program written on IDL, supplementing the wavelet-analysis, delay change between fluxes on separate studied frequencies for each of periodic components has been defined eventually. The average delay for the 8 years periodic component in the range of frequencies of 4.8-8 GHz is about 1 year. In the range of frequencies 8 - to 14.5 GHz the average size of a delay was about 0.5 years. The average delay for all intervals of frequencies for the 3 years periodic components has appeared equal 0.3 years.